2017
DOI: 10.1007/s12197-017-9411-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of public investments and economic growth in Cameroon

Abstract: This study investigates the contribution of public investment to economic growth in Cameroon from 1977 to 2015. It uses the Autoregressive Distributed Lag cointegration (ARDL) approach to estimate a modified version of the production function. The estimates indicate that real gross domestic product, labor force, public investment and private investment are cointegrated. Also based on the estimates, public and private investments have positive and significant effects on real gross domestic product in both the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
3
9
0
3
Order By: Relevance
“…The coefficients of error-correction terms ( ) are negative and statistically significant in both the linear and nonlinear results (see Tables 7 and 8). This confirms the existence of long-run relationship among the variables (Olaniyi & Adedokun, 2020;Ntembe et al, 2018;Banerjee et al, 1998). These results are consistent with the outcomes of ARDL bound tests for linear and nonlinear models as earlier presented in Table 5.…”
Section: Ardl Cointegration Bounds Testsupporting
confidence: 91%
See 1 more Smart Citation
“…The coefficients of error-correction terms ( ) are negative and statistically significant in both the linear and nonlinear results (see Tables 7 and 8). This confirms the existence of long-run relationship among the variables (Olaniyi & Adedokun, 2020;Ntembe et al, 2018;Banerjee et al, 1998). These results are consistent with the outcomes of ARDL bound tests for linear and nonlinear models as earlier presented in Table 5.…”
Section: Ardl Cointegration Bounds Testsupporting
confidence: 91%
“…Following the suggestions of extant studies (Olaniyi & Adedokun, 2020;Olaniyi & Oladeji, 2020;Mohanty, 2019;Ntembe et al, 2018), the short and long-run estimates of linear and nonlinear of error-correction version of ARDL are subjected to a series of robustness checks and diagnostic tests so as to ascertain the reliability of the estimates. Thus, the synopsis of residual diagnostics tests of normality, serial correlation, heteroskedascity and the Ramsey reset test for model specification are provided in Table 9.…”
Section: Diagnostic Testsmentioning
confidence: 99%
“…ugyanezt a megközelítést alkalmazva mi is a neoklaszszikus modellt használjuk az állami és magánberuházások és a pakisztáni gazdasági növekedés közötti kapcsolat vizsgálatára. Aschauer (1989), Albala-Bertrand és Mamatzakis (2001) és Ntembe et al (2017), elméleti modelljét követve a jelen tanulmány szintén az állami beruházásokat és más, a kibocsátást befolyásoló változókat használ. A neoklasszikus modell következő, módosított formáját használjuk:…”
Section: Fogalmi Keretunclassified
“…In the same vein, Ramireez (2009) estimated if the public provision of infrastructure raises labour productivity and economic growth in Argentina and found that public investment do positively affect labour productivity growth. A recent study in this regard is of Ntembe et al, (2017). The study was conducted in cameroon.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…following the same approach, we are also using the neoclassical model to examine the relationship between public and private investment and economic growth for Pakistan. following the theoretical model proposed by Aschauer, (1989), Albala-Bertrand and Mamatzakis, (2001) and Ntembe et al, (2017), the current study also uses public investment and a set of other variables that can affect output. We present below a modified neoclassical model of the form,…”
Section: Conceptual Frameworkmentioning
confidence: 99%